Understanding moderators of consent regarding the sharing of supermarket shopping data in ALSPAC. - Burgess, Romana; Skatova, Anya; Taylor, Poppy (International Journal of Population Data Science, 2024)
Introduction & Background Shopping data is a valuable resource, offering insights into consumer behaviour and health. In recent years, there has been a growing interest in using shopping data for the purposes of health research. However, little is known about the characteristics of those who are willing to share their shopping data with researchers. Objectives & Approach This study aims to investigate the factors that influence individuals' decisions to consent to sharing their shopping data for research purposes. We will leverage data from a cohort study – the Avon Longitudinal Study of Parents and Children (ALSPAC) – to address this question. We will draw upon the responses of a 2018 survey, which asked ALSPAC participants about their use of supermarket loyalty cards, their perceived acceptability of sharing this data with ALSPAC, and their perspectives on potential privacy concerns. Of the 4,462 respondents, 65.4% indicated ownership of at least one major UK supermarket or store loyalty card. Among these, 88.4% expressed a potential willingness to share this data with ALSPAC for research purposes. In the present day – around 2023 – participants have explicitly either granted or withheld consent for the sharing of this data. Our analysis approach will consider factors such as biological gender, ethnicity, education, employment, socioeconomic status, and anxiety as potential moderators to the consent process. We plan to employ a mix of standard statistical methods to analyse sampling biases in the dataset, including regression modelling and correlation tests. Relevance to Digital Footprints Our study will contribute to the growing body of literature on data linkage between cohort studies and digital footprints datasets. Results The findings from this study will offer valuable insights into the factors influencing participants' consent decisions regarding data sharing. We will contribute to ongoing discussions about privacy and the ethical use of digital footprints data, informing the development of more inclusive consent processes in this field. Conclusions & Implications This study will inform consent practices in the realm of digital footprints, identifying and addressing potential barriers to consent, and contributing to the ongoing discourse on the responsible and ethical use of shopping data.